Islamic Ethics and Sustainability in Supply Chain Restructuring Amid Geopolitical Disruption: A Bibliometric Analysis Using SPAR-4-SLR - Azizah Mudrikah (El-Barka, 2025)
In the context of intensifying geopolitical disruptions—from wars and pandemics to resource nationalism and trade sanctions—supply chains have become increasingly fragile and ethically contested. This study investigates the intersection of Islamic ethics and sustainability in supply chain restructuring, with a particular focus on halal and faith-based systems. Using the SPAR-4-SLR protocol and bibliometric tools such as Biblioshiny and VOSviewer, we systematically analyzed 58 peer-reviewed journal articles published between 2010 and 2025, sourced from Scopus, Dimensions, and Google Scholar. The study maps thematic evolutions, key authors, research clusters, and citation patterns. It identifies how core Islamic ethical values—such as ʿadl (justice), amānah (trust), iḥsān (excellence), and maqāṣid al-sharīʿah (objectives of Islamic law)—serve as moral anchors in guiding resilient, transparent, and socially responsible supply chains. Halal traceability, blockchain integration, and green logistics emerged as recurring focal points. Furthermore, the findings emphasize the role of spiritual leadership and Islamic governance models in enhancing supply chain integrity amid crises.